Efforts To Restore Respiratory Function In Patients Who Have Experienced Breathing Or Cardiac Arrest (Basic Life Support) In Victims Who Are Unconscious Regarding The Knowledge Of Nurses As A Form Of Health Services - Dunggio, Abdul Rivai Saleh; Rahmat, Rezqiqah Aulia; Ruben, Sethiana Dewi; Halitopo, Yoel; P, Nur Triningtias; Saputra, M. Khalid Fredy (International Journal of Health Sciences, 2025)
Cardiac arrest is a condition where blood circulation stops due to the failure of the heart to contract effectively. Cardiac arrest is characterized by the absence of a pulse and signs of circulation. The purpose of this study was to find similarities, advantages, and disadvantages regarding the description of knowledge and implementation of basic life support for emergency nurses in emergency installations. This research method uses descriptive correlation. Amount sample in study this is 27 respondents. The results of the study showed that the knowledge of nurses in performing basic life support. Of the 27 respondents studied, 17 people (62.9%) of them had good knowledge, 8 people (29.6%) of them had sufficient knowledge, and 2 people (7.5) of them had insufficient knowledge. The conclusion of the study showed that most of the nurses' knowledge had good knowledge in performing basic life support in installation emergency emergency hospital.